1996
DOI: 10.1055/s-2006-957851
|View full text |Cite
|
Sign up to set email alerts
|

2′-Hydroxycinnamaldehyde from Stem Bark ofCinnamomum cassia

Abstract: 2'-Hydroxycinnamaldehyde, which inhibits farnesyl-protein transferase (FPTase), has been isolated from the stem bark of Cinnamomum cassia Blume. The biologically active agent in the extract has been purified by silica column chromatography and HPLC. The structure of the isolated compound was elucidated on the basis of 500 MHz NMR experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 2 publications
1
26
0
Order By: Relevance
“…2′-Benzoyloxycinnamaldehyde (BCA; Figure 1), currently under preclinical development as an antitumour agent, was originally synthesized as a derivative of 2′-hydroxycinnamaldehyde (HCA; Figure 1) (Kwon et al 1997), a natural product isolated from the stem bark of Cinnamomum cassia Blume (Lauraceae) (Kwon et al 1996). BCA has also been isolated recently from the aerial parts of Pleuropterus ciliinervis Nakai (Polygonaceae) (Kang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2′-Benzoyloxycinnamaldehyde (BCA; Figure 1), currently under preclinical development as an antitumour agent, was originally synthesized as a derivative of 2′-hydroxycinnamaldehyde (HCA; Figure 1) (Kwon et al 1997), a natural product isolated from the stem bark of Cinnamomum cassia Blume (Lauraceae) (Kwon et al 1996). BCA has also been isolated recently from the aerial parts of Pleuropterus ciliinervis Nakai (Polygonaceae) (Kang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The authors' studies further demonstrated that their anti-proliferative activity against tumour cells was mediated by induction of apoptosis via reactive oxygen species (ROS) (Han et al 2004) and inhibition of proteasome (Hong et al 2007). In addition, HCA was reported to have various other pharmacological activities including farnesyl protein transferase inhibition (Kwon et al 1996), anti-inflammatory activity (Lee et al 2005), immunomodulation (Koh et al 1998), and antifungal activity (Kang et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Cinnamaldehyde compounds have found wide applications in food, cosmetic [1,2] or agrochemical [3][4][5][6] and pharmaceutical industries. [7][8][9][10][11][12] Some cinnamaldehyde derivatives exhibit non-linear optical properties. [13][14][15][16][17][18][19][20] Several methods based on the Perkin and Claisen condensations of aromatic aldehydes have been reported for the synthesis of cinnamaldehyde derivatives on the industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…2Ј-Hydroxycinnamaldehyde (HCA), 1 isolated from the stem bark of Cinnamomum cassia, was reported to have an inhibitory effect on farnesyl protein transferase activity in vitro (1). The cinnamaldehydes have also been shown to have various activities such as anti-angiogenic activity (2) and to be immunomodulators (3), CDK4/cyclinD1 kinase (4), and the proliferation of several human cancer cell lines including breast, leukemia, ovarian, lung, and colon tumor cells (5).…”
mentioning
confidence: 99%